Synthesis of Hyperbranched Polymers and Prospects for Application in Oilfield Chemistry - Zhang, Ying; Yu, Weichu (Frontiers in Energy Research, 2022)
Hyperbranched polymer is a kind of polymer with three-dimensional structure, which contains highly branched structure and a large number of modified terminal functional groups. The desired properties can be obtained by modifying the active end groups appropriately. Hyperbranched polymers have been successfully used in the development of oilfield chemicals due to their excellent properties of solubility, rheology, temperature resistance and salt resistance. Therefore, the application of hyperbranched polymer is helpful to the efficient development of oil field. In this paper, the synthesis methods of hyperbranched polymers are reviewed and the advantages and disadvantages of different synthesis methods are analyzed. Furthermore, the research progress of hyperbranched polymers in oilfield chemistry is systematically described, and the advantages and existing problems of their application in polymer flooding as oil displacement agents, demulsification of crude oil, clay hydration expansion inhibition and shale inhibition are discussed. Finally, the application prospect of hyperbranched polymer in drilling chemistry, oil recovery chemistry and gathering and transportation chemistry is forecasted, which is expected to help the popularization and application of hyperbranched polymer in oil field.